The Overseas Experience of Audit Committee and Audit Fees: Empirical Evidence from China. (14th July 2021) - Li, Chengai; Pan, Lin; Chen, Meilan
Abstract : The complexity of audit committee experience, including the overseas experience, has an important impact on corporate governance. In this paper, we study the impact of the overseas experiences of the members of audit committee on audit fees. Our empirical analysis and results show that the audit committee overseas experience can significantly increase audit fees. Further, the positive influence of the audit committee overseas experience on audit fees is more pronounced in state-owned enterprises and regions with weak marketization. In addition, we divide the overseas experience into overseas learning experience and overseas working experience. We find that both types of experience present in the audit committee significantly increase the audit fees. Finally, we find that the audit committee overseas experience can significantly improve the quality of accounting information and play a positive role in corporate governance.